Invited review: Tannins as a potential alternative to antibiotics to prevent coliform diarrhea in weaned pigs. (1st October 2019) - Girard, M.; Bee, G.
Abstract : In addition to a multifactorial etiology of nutritional, social and environmental stressors, post-weaning diarrhea (PWD ) in pigs is often related to infection with specific pathogens such as enterotoxigenic Escherichia coli (ETEC ). In swine farming operations, the incidence of PWD is a global concern and is associated with an unbalanced gut status, resulting in poor performance and high antimicrobial consumption via prophylaxis and metaphylaxis. Increases in antimicrobial resistance are reinforcing an already-urgent need for sustainable, alternative solutions for maintaining optimal gut health in livestock. Tannin-rich plants and extracts contain bioactive compounds that could be of great interest in this respect. This review describes how the use of tannins around weaning could be beneficial for pigs, with special emphasis on the reduction of ETEC-related PWD. An overview of the broad chemical diversity of tannins is presented together with their physicochemical and biological properties, as well as how they may be metabolized in the digestive tract. The pharmacological effects exerted by tannins are summarized; more precisely, the possible mechanisms by which tannins can disrupt the different steps of the pathogenesis of ETEC-related PWD are highlighted. The factors affecting the bioactivity of tannins are also discussed, shedding light on the importance of chemical structure among different tannins.